SELF-CONTROL, PEER ENVIRONMENT, PARENTAL SUPPORT AND TEACHER COMPETENCE ON STUDENTS' LEARNING MOTIVATION AT SMKN 2 SUKOHARJO - Kusrini, Eny; Mursito, Bambang; Istiatin, Istiatin (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2025)
The background of this research is that students' studying motivation in Skill Competency of Livestock Agribusiness of SMK Negeri 2 Sukoharjo is still classified low. The purpose of this research is to know the effect of self-control, peer social environment, parents' support and teachers' competence for students' studying motivation of Skill Competency of Livestock Agribusiness of SMK Negeri 2 Sukoharjo. The method of this research is using quantitative research design. The population is all X and XII students of Skill Competency of Livestock Agribusiness of SMK Negeri 2 Sukoharjo. The number is 139 students. The sampling technique in this research is Census Technique with the number of samples is 139 respondents. The technique of collecting data is using questionnaires. The technique of analyzing data is using statistical analysis namely multiple linear regression test, F test, t test, and determination coefficient. The results show that self-control, peer social environment, parents' support and teachers' competence significantly influence students' studying motivation of Skill Competency of Livestock Agribusiness of SMKN Negeri 2 Sukoharjo. The suggestions from this research are that the students are necessary to improve self-control, the parents should give support to their sons or daughters, and the teachers are necessary to improve competences according to main duties, so they will make students' studying motivation better than before.